Metabolic aspects of latex regeneration in situ for three Hevea clones - Serres E; Clement A; Commerce J; Jacob J L; Lacrotte R; Prevot J C (Indian Journal of Natural Rubber Research, 1994)
Some biological parameters of latex, according to the interval between two tappings, were studied in clones PB 235, PB 217 and GT 1 with a view to having a better understanding of metabolic controls and regulation systems involved in latex regeneration. Three days interval is needed after tapping to obtain maximal yield indicating complete latex regeneration in situ for these clones. Analyses of total solids content in the latex and study of other parameters linked to energetic processes of laticiferous cells, such as thiols and inorganic phosphorus content, sugar content and their variations, organic N and total P and ionic (K and Mg) elements were effected. The results obtained lead to link the variations observed in the metabolic activity of laticiferous cells with the tapping intervals and the clones. The results emphasise the importance of metabolic activity in latex regeneration and thus in production. Also, they can explain the differences among these clones in their response to stimulation. They underline the necessity to exploit each Hevea clone according to the metabolic typology of its laticiferous system.
Keywords: Hevea brasiliensis; Latex parameters; Latex regeneration; Metabolic activity